LUKA WARISAN: IMPLIKASI BUDAYA PATRIARKI PADA KASUS KEKERASAN DALAM RUMAH TANGGA DI KABUPATEN BONE - A. Aswar; Ahmad Nugraha Abrar; Rahmat Hidayat; Nani Suciati; Asria Wahyuni (AN-NISA, 2025)
The low status of women in a patriarchal culture renders them vulnerable to discrimination and violence within both the social and domestic spheres. The Bugis community maintains a wide range of cultural traditions, including a deeply rooted patriarchal paradigm. This imbalance of power relations significantly increases the likelihood of women experiencing violence, particularly domestic violence (KDRT). This article aims to analyze the implications of patriarchal culture in cases of domestic violence within the Bugis community residing in Bone Regency. The research employs an empirical legal method, examining law as written norms while also analyzing legal behavior within society. The findings reveal that the patriarchal culture of the Bugis community in Bone Regency has direct implications for domestic violence. Unequal power relations, restrictions on women’s participation in the social sphere, and the persistence of the siri’ concept, alongside conservative religious interpretations, sustain patriarchal behavior within Bugis society.